Giving it a burl: towards the integration of genetics, isotope chemistry, and osteoarchaeology in Cape York, Tropical North Queensland, Australia. Issue 4 (8th August 2019) - Collard, Mark; Wasef, Sally; Adams, Shaun; Wright, Kirsty; Mitchell, R. John; Wright, Joanne L.; Wrobel, Gabriel; Nagle, Nano; Miller, Adrian; Wood, Rachel; Pietsch, Timothy J.; Van Holst Pellekaan, Sheila; et al.
ABSTRACT: In this paper we outline a worked example of the combined use of genetic data and archaeological evidence. The project focuses on Queensland's Cape York Peninsula and has two goals. One is to shed new light on the population history of the region. The other is to develop a methodology to facilitate repatriation of the remains of Aboriginal Australians. After providing some background to the project and outlining its main activities, we summarize our key findings to date. Subsequently, we discuss what the project has taught us about the prehistory of Cape York, the potential for DNA research and isotope chemistry to assist research institutions and Aboriginal communities with the repatriation of unaffiliated remains, and the process of conducting combined genetic and archaeological research.